Effects of a selected exercises program on quality of life in elderly women - Mansoureh Zamanian; Nader Rahnama; Shahram Lenjan Nejadian; Mohammad Reza Salamat; Mansour Salesi (Vesnu Publications, 2012)
Introduction: Osteoporosis is the most common type of bone disease that affects the skeletal system especially in older people. In elderly population, reduction in bone mineral density (osteoporosis) is often associated with a reduced health-related Quality of Life. The present study aimed to investigate the effect of a selected exercises program on quality of life in elderly women with osteoporosis. Materials and Methods: Twenty- seven women with osteoporosis (Mean age ± SD, 58 ± 6 years) who were referred to Isfahan osteoporosis diagnostic center divided into two groups: intervention (n = 14) and control (n = 13) groups. The experimental group received the following intervention: balance, strength training and range of motion exercises for 8- weeks (three sessions per week) .Control group did not receive any intervention. Quality of life was measured using the QUALEFFO-41 questionnaire just before and after exercise program. Independent and paired sample t-test were used to analyze the data. Results: In experimental group, a significant difference (P < 0/05) was observed before and after exercise program in pain (30/7 ± 17 vs. 15/4 ± 11), mobility (23/1 ± 8 vs. 17/6 ± 7), social activities (27/9 ± 13 vs. 20/16 ± 8), general health perception (51/2 ± 21 vs. 35/1 ± 16), mental function (20/8 ± 6 vs. 15/1 ± 5). There is no significant difference (P > 0/05) in household activities and ADLs. Also, no significant difference was observed in control group (P > 0/05). Although, in pre test, the observed difference was not statically significant between control and experimental groups (P > 0/05), but significant difference was found in post test (P < 0/05). Conclusion: It seems that an exercise program could improve health-related quality of life in elderly women with osteoporosis, therefore this exercise program can be considered as an appropriate treatment regimen for such patients. Keywords: Elderly woman, Osteoporosis, Quality of life, QUALEFFO-41 questionnaire, Regular exercises program